MARCO CONCEPTUAL DEL TALLER “PONER LÍMITES” PARA PADRES DEL NIVEL INICIAL - Roberto, Galasso (European Scientific Journal, ESJ, 2015)
Every practice needs a theory that can both enrich each other. Therefore, when I drafted the workshop "Putting Limits" (TPL) aimed at parent`s early education, the first thing I posted was a conceptual framework to guide the practice, and at the same time, parameters to evaluate the results. The TPL originated because teachers identified the main problem to work in classroom to be that students have "no limits" (don`t wait for their turn, bother, ignore, rise without permission, etc.), and their parents have some difficulty in getting their children to obey them. Being a member of GPS / ENSRP, I delved on the subject and reflections I have made based on contributions from other authors. Also, I employed Transactional Analysis which allowed me to develop conceptual assumptions that may enrich dialectically with lines of action and research on this problem by similar workshops in different contexts. However, this paper identifies and evaluates these fundamental concepts.